Associations of Pre-Diagnostic Serum Levels of Total Bilirubin and Albumin With Lung Cancer Risk: Results From the Southern Community Cohort Study - Yoon, Hyung-Suk; Shu, Xiao-Ou; Shidal, Chris; Wu, Jie; Blot, William J.; Zheng, Wei; Cai, Qiuyin (Frontiers in Oncology, 2022)
Previous studies conducted among European and Asian decedents reported inverse associations between serum total bilirubin and albumin and lung cancer risk. No study has been conducted among African Americans or low-income European Americans. This study included 522 incident lung cancer cases and 979 matched controls nested in the Southern Community Cohort Study, a cohort study of predominantly low-income African and European Americans. Serum levels of total bilirubin and albumin, collected up to 11 years prior to case diagnoses, were measured by a clinical chemistry analyzer. Conditional logistic regression models were applied to evaluate associations of total bilirubin and albumin with lung cancer risk. Overall, serum levels of total bilirubin (ORT3 vs. T1 = 0.96, 95% CI: 0.66-1.39) was not significantly associated with the risk of lung cancer. A higher serum total bilirubin level was significantly associated with a decreased risk of lung cancer among participants who were diagnosed within two years following sample collection (ORT3 vs. T1 = 0.36, 95% CI: 0.15-0.87) and among former/never smokers (ORT3 vs. T1 = 0.54, 95% CI: 0.32-0.93). Serum level of albumin was significantly associated with overall risk of lung cancer (ORT3 vs. T1 = 0.70, 95% CI: 0.50-0.98), and among African Americans (ORT3 vs. T1 = 0.62, 95% CI: 0.41-0.96) but not European Americans. Our results indicate that, in a low-income African American and European American population, serum level of total bilirubin may be related to lung cancer progression and differ by smoking status. The association of serum albumin level with lung cancer risk may differ by race. Further studies are warranted to confirm these results.